Action of BjussuMP-II, a snake venom metalloproteinase isolated from Bothrops jararacussu venom, on human neutrophils. (15th January 2023) - K, Lisita; M.D.S, Silva; H.M, Santana; Y.J, Ikenohuchi; M.V, Paloschi; C.M.A, Rego; S.N, Serrath; A.M, Lima; M.N, Sousa; A.M, Soares; S.S, Setúbal; J.P, Zuliani
Abstract: Snake venom metalloproteinases (SVMPs) are enzymatic proteins present in large amounts in snake venoms presenting proteolytic, hemorrhagic, and coagulant activities. BjussuMP-II, a class P–I SVMP, isolated from the Bothrops jararacussu snake venom does not have relevant hemorrhagic activity but presents fibrinolytic, fibrinogenolytic, antiplatelet, gelatinolytic, and collagenolytic action. This study aimed to verify the action of BjussuMP-II on human neutrophil functionality focusing on the lipid bodies formation and hydrogen peroxide production, the release of dsDNA through colorimetric and microscopic assays, and cytokines by immunoenzymatic assays. Results showed that BjussuMP-II at concentrations of 1.5 up to 50 μg/mL for 24 h is not toxic to human neutrophils using an MTT assay. Under non-cytotoxic concentrations, BjussuMP-II can induce an increase in the formation of lipid bodies, production of hydrogen peroxide and cytokines [tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6) and interleukin-8 (IL-8)] liberation and, the release of dsDNA to form NETs. Taken together, the data obtained show for the first time that BjussuMP-II has a pro-inflammatory action and activates human neutrophils that can contribute to local damage observed in snakebite victims. Graphical abstract: Image 1 Highlights: BjussuMP-II does not interfere with human neutrophil viability. BjussuMP-II induces lipid bodies formation. BjussuMP-II induces cytokines, hydrogen peroxide and DsDNA release.